Troubled regions and failing states the clustering and contagion of armed conflicts - Harpviken, Kristian Berg. (Bingley, UK : Emerald, 2010)
Is the phenomenon of state failure better understood through a focus on the regional context? To what extent may studies of regional security benefit from a focus on the capacities and vulnerabilities of the states involved? These are the questions addressed in this volume of Comparative Social Research. Substantially, this special issue operates at the intersection of the larger debates on state failure and on regional (in-) security, relating to various perspectives within each of these. State failure, manifesting itself in the inability of a state to maintain its monopoly of violence, has become a widespread phenomenon in several regions of the world. While the weakness of the institutions of the state in question is an obvious dimension of state failure, there is also an important international dimension. In many of these cases, conflicts are interwoven and violence spills across borders.
Troubled regions and failing states: introduction / Kristian Berg Harpviken -- The theory of failure and the failure of theory: 'state failure', the idea of the state and the practice of state building / Stein Sundstøl Eriksen -- Strong chieftaincies out of weak states, or elemental power unbound / Georgi Derluguian and Timothy Earle -- Corruption and conflict: contrasting logics of collective action / Jens Christopher Andvig -- Colliding state-building projects and regional insecurity in post-Soviet space: Georgia versus Russia in South Ossetia / S. Neil MacFarlane -- Transforming West African militia networks for postwar recovery / William Reno -- Regional security: demarcating theoretical and empirical borders / Rodrigo Tavares -- Strong states in a troubled region: anatomies of a Middle Eastern regional conflict formation / Reinoud Leenders -- State strength on the Ethiopian border: cross-border conflicts in the Horn of Africa / J. Andrew Grant -- Natural resources, international regimes and state-building: diamonds in West Africa / J. Andrew Grant -- Re-examining the 'colour revolutions': the turn of the tide from Belgrade to Ulan Bator / Pavel K. Baev -- Caught in the middle? Regional perspectives on Afghanistan / Kristian Berg Harpviken -- Power, security and regional conflict management in Southern Africa and South Asia / Laurie Nathan -- State responses to transnational challenges: the evolution of regional security organisations in Africa / Karin Dokken -- Webs of war: managing regional conflict formations in West Africa and Central Africa / Ståle Ulriksen.
Description based on print version record.
Includes bibliographical references.
Print version record
Keywords: Failed states; Failed states -- Regional disparities; National security; Political violence; Political stability; Regionalism; Social research & statistics; Sociology; Social Science -- Research; Social Science -- Sociology -- General; Social Science -- General